Impact of Pulse Oximetry Screening on the Detection of Duct Dependent Critical Congenital Heart Disease in Neonate (Bangladesh Journal of Child Health, 2017)
Background: Screening for congenital heart diseases (CHD) in newborn babies aid in early recognition, with the prospect of improved outcome. Currently there is no effective screening protocol for this condition. Pulse oximetry is highly specific for detection of critical CHD with moderate sensitivity that meets criteria for universal screening.Objective: To evaluate the use of pulse oximetry as a screening tool in early detection of critical CHD specially duct dependent critical CHD in asymptomatic newborn babies.Methodology: A cross sectional study conducted in Dhaka Shishu (Children) Hospital from October 2014 to June 2015. Newborns attended outpatient department or admitted in different wards with having gestational age >35 weeks and age between 24-48 hours were included and pulse oximetry screening was done. Oxygen saturation measurement